Mesenchymal Stem Cell-Derived Extracellular Vesicles Ameliorates Hippocampal Synaptic Impairment after Transient Global Ischemia - Deng, Mingyang; Xiao, Han; Zhang, Hainan; Peng, Hongling; Yuan, Huan; Xu, Yunxiao; Zhang, Guangsen; Hu, Zhiping (Frontiers in Cellular Neuroscience, 2017)
Recent studies have found that administration of stem cells or extracellular vehicles (EVs) derived from stem cells exert neuroprotective effects after transient global ischemia. However, the underlying mechanisms of this effect remain unclear, especially at the level of synaptic functions. In this study, we compared the suppressive effects on COX-2 upregulation by EVs derived from bone marrow mesenchymal stem cells (BMSC-EV), adipose tissue MSC (AdMSC-EV) and serum (serum-EV). Then we examined whether BMSC-EVs could restore functional integrity of synaptic transmission and plasticity. Mice were randomly assigned to four groups: sham, sham with EV treatment, ischemia and ischemia with EV treatment. EVs were administered by intracerebroventricular injection (ICVI). We examined the consequence of transient global ischemia on pre- and post-synaptic functions of the hippocampal CA3-CA1 synapses at basal level, and long-term potentiation (LTP), an activity-dependent form of synaptic plasticity. Then we tested the therapeutic effects of EVs on these synaptic deficits. Meanwhile, Morris water maze test was performed to examine the efficacy of EVs in rescuing ischemia-induced impairments in spatial learning and memory. EV treatment significantly restored impaired basal synaptic transmission and synaptic plasticity, and improved spatial learning and memory compared with the control group. In addition, EVs significantly inhibited ischemia-induced pathogenic expression of COX-2 in the hippocampus. EVs exert ameliorating effects on synaptic functions against transient global cerebral ischemia, which may be partly attributed to suppression of COX-2 pathogenic expression.